-n+1-7n=9-7n

Simple and best practice solution for -n+1-7n=9-7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -n+1-7n=9-7n equation:


Simplifying
-1n + 1 + -7n = 9 + -7n

Reorder the terms:
1 + -1n + -7n = 9 + -7n

Combine like terms: -1n + -7n = -8n
1 + -8n = 9 + -7n

Solving
1 + -8n = 9 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
1 + -8n + 7n = 9 + -7n + 7n

Combine like terms: -8n + 7n = -1n
1 + -1n = 9 + -7n + 7n

Combine like terms: -7n + 7n = 0
1 + -1n = 9 + 0
1 + -1n = 9

Add '-1' to each side of the equation.
1 + -1 + -1n = 9 + -1

Combine like terms: 1 + -1 = 0
0 + -1n = 9 + -1
-1n = 9 + -1

Combine like terms: 9 + -1 = 8
-1n = 8

Divide each side by '-1'.
n = -8

Simplifying
n = -8

See similar equations:

| -3+6x=x+7 | | z+3.6=2.5 | | -0.24p+1.602=1.29 | | 1X+4Y=58 | | -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= | | 10g=1100 | | x+4+x+2+x+5=2(x+1)+2(x+3) | | 10=1100 | | 3x-6=-14-7+6x+6 | | m^2-6m-33=-6 | | 5x-2=2x-35 | | 4x=38-2x+8 | | 5n^2-50n+105= | | Gsquared+3g=70 | | -10(-m)= |

Equations solver categories